Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'm taking a course on stochastic analysis. I'm stuck on the very first problem of the lecture notes:

$\lim_{n \to \infty} \left(1+\frac{\lambda}{n} + o(n^{-1})\right)^n = \exp(\lambda)$

Prior to the problem, the lecturer mentioned infinitesimal functions and introduced the Taylor series. I'm not sure how they are useful in proving the above, however.

I thought about taking the log of both sides:

$\lim_{n \to \infty} n\log \left(1+\frac{\lambda}{n} + o(n^{-1})\right) = \lambda$

then substituting $m=n^{-1}$ to get:

$\lim_{m \to 0} m^{-1} \log \left(1+\lambda m + o(m)\right) = \lambda$

I'm lost on where to go next. Does anybody have any ideas?

share|improve this question
3  
As $m$ approaches 0, you can write $\log(1 + x)$ in terms of its taylor expansion. –  TenaliRaman Dec 27 '12 at 11:04
    
Where does $x$ come from? –  misha Dec 27 '12 at 11:25
1  
$x$ in this case is $\lambda m + o(m)$. –  TenaliRaman Dec 27 '12 at 11:29
add comment

2 Answers 2

up vote 1 down vote accepted

Write $$A = \lim_{n \to \infty} \left(1+\frac{\lambda}{n} + f(n)\right)^n$$ where $f(n) = o(n^{-1})$.

Then $$\log(A) = n\log\left( \lim_{n \to \infty} \left(1+\frac{\lambda}{n} + f(n)\right)\right)$$

Since $\lim_{n \to \infty} |f(n)| \leq \lim_{n \to \infty}\epsilon/n = 0$. It follows that

$$\log(A) = \log \left( \lim_{n \to \infty} \left(1+\frac{\lambda}{n}\right)^n\right)$$

and therefore:

$$ A = \exp(\lambda)$$

share|improve this answer
    
Could you explain the reasoning behind the final step (the "therefore")? It's not obvious to me why $\lim_{n\to\infty}\left(1+\frac{\lambda}{n}\right)^n = \exp(\lambda)$. –  misha Dec 27 '12 at 11:37
    
This holds by definition. en.wikipedia.org/wiki/Exponential_function#Formal_definition –  01000100 Dec 27 '12 at 11:42
    
Ah, that's the part I was missing. Thank you. –  misha Dec 27 '12 at 11:48
add comment

You can show and use the following inequality: $$\forall t\geqslant 0,\quad t-\frac{t^2}2\leqslant \log(1+t)\leqslant t.$$ It's classical and actually, it's a bound on the Taylor's remainder. But we can prove it directly.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.